Unfair labour practice on staff in primary health care facilities, North West province, South Africa: A qualitative study - Maserapelo G. Serapelwane; Eva M. Manyedi (AOSIS, 2022)
Background: Unfair labour practices on staff is a worldwide concern which creates conflicts and disharmony among health workers in the workplace. It is found that, nursing staff members are unfairly treated without valid reasons in primary health care (PHC) facilities and predominantly in the developing countries and South Africa is not an exception. Objectives: The purpose of the study was to explore and describe the experiences of operational managers regarding unfair labour practices on staff by their local health area managers, and describe the perceptions of operational managers towards such treatment. Method: A qualitative, descriptive, exploratory and contextual research approach was considered appropriate for the study. The population of the study comprised operational managers working in PHC facilities in the North West province, South Africa. Purposive sampling was used to select participants for the study and focus group interviews used to interview 23 operational managers. Ethical measures were applied throughout the study. Results: The six phases of thematic analysis were used to analyse the data collected for the study. Two themes that emerged are experiences of factors related to unfair labour practices in the PHC facilities and the perceptions regarding how to improve their working conditions. The categories that were found in the first themes were favouritism and discrimination. In the second theme, in-service training and transparency regarding staff training and development emerged. Recommendations comprised, among others, training on the concepts of equality in the workplace, and reinforcement of transparency regarding granting of study leave and attending workshops. Conclusion: Operational managers in the PHC facilities experienced unfair labour practices as evidenced by favouritism and discrimination.